SIAPKAH KONSELOR KITA MELAKUKAN KONSELING/TERAPI KELUARGA? - Siregar, Alfin (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
The growth of children from infants to adolescents, the development of children from unrealistic to realistic is an accumulation of children's life experiences. Therefore, the problems faced by children (school age / students) are basically inseparable from the realistic lives of students as part of family members. This paper aims to analyze the discipline of students in schools / madrasah. The methodology used in this study is based on the phenomenology approach, where data is obtained through in-depth interviews, so the presence of researchers to acquare information is a necessity. The results of this study indicate that the educational problems experienced by students (truancy, low interest in learning, and disrespectful attitude towards the teacher) have a strong relationship to students' family problems. Communication, problem solving skills, roles in the family to the parenting style used by the family, turned out to be the cause of problems in students at school. Parents' expectations for educational institutions are too excessive, such as schools that are responsible for children's lives. In contrast, counselors in schools often intervene with students without grasping at students' problems holistically. Tug of war between family and school (counselor) is one of the main issues that must be taken to create a socializing education.